Negative electrode material, preparation method thereof, and battery

CN122889731APending Publication Date: 2026-10-09LISHEN (QINGDAO) NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611322459.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

但是目前的石墨材料存在比容量、压实、循环、快充性能等难以兼具的问题,因此,亟需一种性能更均衡高效的负极材料

Benefits of technology

[0014]从上面所述可以看出,本申请提供了一种负极材料及其制备方法、电池,所述负极材料包括内核、包覆内核的第一壳层以及包覆第一壳层的第二壳层;内核的材料包括致密化天然石墨和人造石墨混合的二次颗粒复合石墨,第一壳层的材料包括石墨烯,第二壳层的材料包括第一沥青。可通过混合造粒技术将致密化天然石墨与人造石墨混合造粒得到二次颗粒天然、人造复合石墨,再通过材料融合和双层包覆技术对复合石墨进行石墨烯及沥青双层包覆,制得核壳结构的负极材料,经测试,该负极材料比容量>370mAh/g,首次效率>92%,同时快充和循环性能优异,解决了石墨材料高能量密度、高快充性能及长循环寿命难以兼具的问题。该负极材料及其制备方法、电池,结构简单,制作方便,具有高比容量、高压实、高首效、长循环寿命及高倍率性能,同时成本较低。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889731A_ABST
    Figure CN122889731A_ABST
Patent Text Reader

Abstract

The application provides a negative electrode material and a preparation method and a battery thereof. The negative electrode material comprises a core, a first shell layer covering the core, and a second shell layer covering the first shell layer. The material of the core comprises secondary particle composite graphite mixed by densified natural graphite and artificial graphite. The material of the first shell layer comprises graphene. The material of the second shell layer comprises first pitch. The negative electrode material and the preparation method and the battery thereof are simple in structure, convenient to manufacture, high in specific capacity, high in compaction, high in initial efficiency, long in cycle life, high in rate performance, and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and in particular to a negative electrode material, its preparation method, and a battery. Background Technology

[0002] In recent years, with the continuous development of electronic products and electric vehicles, the demand for higher energy density, faster charging performance, and longer cycle life of lithium-ion batteries has become increasingly urgent. Graphite, as the mainstream anode material for lithium-ion batteries, although it does not directly provide lithium ions, has a significant impact on the energy density, power performance, and cycle performance of lithium-ion batteries. However, current graphite materials suffer from difficulties in simultaneously achieving optimal performance in specific capacity, compaction, cycle life, and fast charging. Therefore, a more balanced and efficient anode material is urgently needed. Summary of the Invention

[0003] In view of this, the purpose of this application is to provide a negative electrode material and its preparation method, as well as a battery, to solve the above-mentioned technical problems.

[0004] In a first aspect, this application provides a negative electrode material, comprising a core, a first shell covering the core, and a second shell covering the first shell; the core is made of a secondary particle composite graphite composed of a mixture of densified natural graphite and artificial graphite, the first shell is made of graphene, and the second shell is made of a first bitumen.

[0005] A second aspect of this application provides a method for preparing the negative electrode material described in the first aspect, comprising: preparing a precursor of densified natural graphite; mixing and granulating the precursor with artificial graphite to obtain secondary particle composite graphite; fusing the secondary particle composite graphite with graphene to obtain a fused material; and mixing the fused material with a first bitumen and then performing a carbonization treatment to obtain the negative electrode material.

[0006] Furthermore, the preparation of the precursor for densified natural graphite includes: mixing natural graphite microspheres with a second bitumen to obtain a first mixture; and subjecting the first mixture to a densification treatment under pressure and temperature to obtain the precursor for densified natural graphite.

[0007] Furthermore, the average particle size of the natural graphite microspheres is 5μm-15μm; the softening point of the second asphalt is 60℃-90℃, and the quinoline insoluble content is ≤1%; the mass ratio of the natural graphite microspheres to the second asphalt is 100:(8-20); the natural graphite microspheres and the second asphalt are mixed in a mixer at a speed of 150r / min-300r / min for a mixing time of 60min-120min; the densification treatment is carried out at a pressure of 100MPa-150MPa, a temperature of 250℃-350℃, and a treatment time of 60min-120min.

[0008] Further, the step of mixing and granulating the precursor with artificial graphite to obtain secondary particle composite graphite includes: crushing and shaping coke to obtain coke powder; mixing the coke powder, the precursor, and third asphalt to obtain a second mixture; granulating the second mixture according to a heating curve to obtain granulated composite powder; and graphitizing the granulated composite powder to obtain secondary particle composite graphite.

[0009] Further, the average particle size of the coke powder is 8μm-10μm; the softening point of the third pitch is 150℃-250℃, and the quinoline insoluble content is ≤1%; the mass ratio of the coke powder to the precursor is 30:70-75:25, and the mass ratio of the sum of the coke powder and the precursor to the third pitch is 100:(3-20); the heating curve is a rapid heating from room temperature to 420℃-480℃, then a slow heating to 680℃-720℃, and a holding time of 3h-10h; the graphitization treatment temperature is 2800℃-3200℃, and the time is 2h-10h.

[0010] Furthermore, the step of fusing the secondary particle composite graphite with graphene to obtain a fused material includes: dissolving graphene in a solvent to prepare a graphene solution; adding the secondary particle composite graphite and a binder to the graphene solution to obtain a mixed slurry; and subjecting the mixed slurry to a fusion reaction to obtain the fused material.

[0011] Further, the solvent includes one or more of water, methanol, ethanol, or N-methylpyrrolidone, and the mass ratio of graphene to the solvent is (5-8):100; the binder includes one or more of sodium hydroxymethyl cellulose, stearic acid, polyvinyl alcohol, phenolic resin, epoxy resin, glucose, or starch, and the mass ratio of the secondary particle composite graphite, the graphene, and the binder is 100:(5-20):(1-10); the mixed slurry is fused in a fusion machine with a rotation speed of 50 r / min-200 r / min and a fusion time of 5 min-30 min.

[0012] Furthermore, the softening point of the first asphalt is 60℃-80℃, and the quinoline insoluble content is ≤1%; the mass ratio of the first asphalt to the secondary particle composite graphite is (2-10):100; the fusion is carbonized in a tube furnace under inert gas protection, the inert gas including nitrogen and / or argon; the carbonization temperature is 800℃-1200℃, the heating rate is 5℃ / min-10℃ / min, and the treatment time is 1h-10h.

[0013] A third aspect of this application provides a battery comprising: a positive electrode, a separator, a negative electrode, and an electrolyte, wherein the negative electrode comprises the negative electrode material described in the first aspect above.

[0014] As described above, this application provides a negative electrode material, its preparation method, and a battery. The negative electrode material includes a core, a first shell layer covering the core, and a second shell layer covering the first shell layer. The core material comprises a secondary particle composite graphite composed of a mixture of densified natural graphite and artificial graphite. The first shell layer comprises graphene, and the second shell layer comprises first pitch. Secondary particle natural and artificial composite graphite can be obtained by mixing and granulating densified natural graphite and artificial graphite using a mixing granulation technique. Then, the composite graphite is coated with graphene and pitch using a material fusion and double-layer coating technique to obtain a core-shell structured negative electrode material. Testing shows that this negative electrode material has a specific capacity >370mAh / g, an initial efficiency >92%, and excellent fast charging and cycle performance, solving the problem of graphite materials having difficulty simultaneously achieving high energy density, high fast charging performance, and long cycle life. This negative electrode material, its preparation method, and the battery have a simple structure, are easy to manufacture, and possess high specific capacity, high compaction, high initial efficiency, long cycle life, and high rate performance, while also having a low cost. Attached Figure Description

[0015] To more clearly illustrate the technical solutions in this application or related technologies, the drawings used in the description of the embodiments or related technologies will be briefly introduced below. Obviously, the drawings described below are only embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0016] Figure 1 This is an electron microscope image of the negative electrode material in Embodiment 1 of this application. Detailed Implementation

[0017] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with specific embodiments and the accompanying drawings.

[0018] It should be noted that, unless otherwise defined, the technical or scientific terms used in the embodiments of this application should have the ordinary meaning understood by one of ordinary skill in the art to which this application pertains. The terms "first," "second," and similar terms used in the embodiments of this application do not indicate any order, quantity, or importance, but are merely used to distinguish different components. Terms such as "comprising" or "including" mean that the element or object preceding the word encompasses the elements or objects listed after the word and their equivalents, without excluding other elements or objects. Terms such as "connected" or "linked" are not limited to physical or mechanical connections, but can include electrical connections, whether direct or indirect. Terms such as "upper," "lower," "left," and "right" are only used to indicate relative positional relationships; when the absolute position of the described object changes, the relative positional relationship may also change accordingly.

[0019] Lithium-ion batteries have been widely used in electronics and electric vehicles due to their advantages such as high energy density, high power performance, long cycle life, and environmental friendliness. In recent years, the demand for higher energy density, faster charging performance, and longer cycle life of lithium-ion batteries has become increasingly urgent.

[0020] Graphite, as a mainstream anode material, does not directly provide lithium ions, but it has a significant impact on the energy density, power performance, and cycle performance of lithium-ion batteries. Natural graphite has advantages such as high specific capacity, good processability, and low price; however, due to the porosity within its particles, natural graphite is prone to uneven stress during charge and discharge, resulting in poor cycle life. Synthetic graphite exhibits superior electrical properties, with good power performance and long cycle life, but its specific capacity is relatively low, generally not exceeding 360 mAh / g (the ideal graphite specific capacity is 372 mAh / g), and its cost is relatively high.

[0021] Some technologies propose a high-capacity, fast-charging composite anode material for lithium-ion batteries. This involves mixing and granulating primary particles (after grinding and shaping needle-shaped coke powder) with primary spherical natural graphite particles, followed by graphitization to obtain composite graphite. The graphitized secondary particles are then coated with asphalt to obtain a composite graphite anode material with the properties of both natural and artificial graphite, exhibiting a stable material structure. This composite graphite anode material achieves a discharge capacity of 365 mAh / g and an initial efficiency >93%. While this capacity is improved compared to ordinary artificial graphite, it still falls significantly short of the theoretical capacity limit of graphite (372 mAh / g). Furthermore, the addition of natural graphite reduces the material's cycle life.

[0022] To address the challenge of achieving high specific capacity, high compaction, long cycle life, and fast charging performance simultaneously in graphite materials, this application provides a novel composite graphite material and its preparation method. The internal densification treatment improves the cycle performance of the natural graphite component, while the natural and artificial secondary particle composite graphite is coated with graphene and pitch in a double layer to further enhance the specific capacity of the material, reaching over 372 mAh / g, and exhibiting excellent cycle life.

[0023] The following describes specific embodiments in conjunction with... Figure 1 The technical solution of this application will be described in detail below.

[0024] In some embodiments of this application, a negative electrode material is provided, including a core, a first shell covering the core, and a second shell covering the first shell; the material of the core includes secondary particle composite graphite of a mixture of densified natural graphite and artificial graphite, the material of the first shell includes graphene, and the material of the second shell includes a first bitumen.

[0025] The anode material has a core-shell structure. The core consists of a secondary particle composite graphite made up of a mixture of densified natural graphite and artificial graphite, which can improve the isotropy of the material and combine the advantages of high capacity, high compaction and low cost of natural graphite with the advantages of high performance and long cycle life of artificial graphite. At the same time, natural graphite can provide lubrication for artificial graphite during rolling, further improving the powder compaction density of the composite material. Furthermore, the densified natural graphite can further improve the cycle performance.

[0026] The shell of the negative electrode material, from the inside out, consists of graphene and a first bitumen layer, such as petroleum bitumen and / or coal tar bitumen. Due to the large interlayer spacing of the graphene coating, the Li+ transport rate can be improved, impedance reduced, and fast-charging performance enhanced through surface coating. Simultaneously, because graphene possesses both interlayer lithium storage and defect adsorption lithium storage mechanisms, it can accommodate more Li+ compared to graphite structures. + This significantly improves the specific capacity of the material, but excessive graphene interfaces can lead to a decrease in the initial efficiency. Adding a pitch coating to the graphene-coated surface can prevent excessive graphene interfaces from being exposed to the electrolyte, improving the interfacial state of the graphite material and reducing the Li-induced efficiency drop during charging and discharging. + This reduces material loss and improves initial efficiency, solving the problem of reduced initial efficiency caused by graphene coating; simultaneously, because the spacing between the asphalt coating layers is also relatively large, it can further improve Li + The high transmission rate enables the material to possess high specific capacity, high initial efficiency, and excellent fast-charging performance. The synergistic effect of graphene coating and pitch coating complements each other, significantly increasing the material's specific energy and greatly enhancing its fast-charging performance.

[0027] Tests showed that the initial discharge specific capacity of this negative electrode material was >370mAh / g, and the powder compaction density was >1.9g / cm³. 3 The initial coulombic efficiency is >92%, the constant current charge ratio during 3C fast charging is >83%, and the capacity retention rate after 2000 cycles at 1C at room temperature is >85%. This anode material has high specific capacity, high compaction, high initial efficiency, long cycle life, and high rate performance, while also being relatively low in cost.

[0028] In some embodiments of this application, a method for preparing a negative electrode material is provided, comprising: preparing a precursor of densified natural graphite; mixing and granulating the precursor with artificial graphite to obtain secondary particle composite graphite; fusing the secondary particle composite graphite with graphene to obtain a fused material; and mixing the fused material with a first bitumen and then performing a carbonization treatment to obtain the negative electrode material.

[0029] Densification of natural graphite, for example using asphalt filling, involves mixing densified natural graphite with raw material coke powder (artificial graphite) and granulating the mixture to obtain granulated composite powder. This powder is then graphitized to obtain secondary granulated composite graphite. The secondary granulated composite graphite is then coated with graphene, followed by asphalt coating, ultimately yielding a graphene-asphalt double-layered natural and artificial graphite composite material. The resulting anode material exhibits high specific capacity, powder compaction density, and initial efficiency, along with excellent cycle life and rate performance. Furthermore, the process is simple and suitable for large-scale industrial production.

[0030] In some embodiments, the preparation of the precursor of densified natural graphite includes: mixing natural graphite microspheres with a second bitumen to obtain a first mixture; and subjecting the first mixture to a densification treatment under pressure and temperature to obtain the precursor of densified natural graphite.

[0031] The average particle size D50 of the natural graphite microspheres is 5μm-15μm, for example, 5μm, 10μm or 15μm, preferably 8μm-10μm. The second bitumen is, for example, petroleum bitumen and / or coal tar bitumen, with a softening point of 60℃-90℃, for example, 60℃, 70℃, 80℃ or 90℃, and a quinoline-insoluble content (the component in bitumen insoluble in quinoline) ≤1%. The mass ratio of natural graphite microspheres to the second bitumen is 100:(8-20), for example, 100:8, 100:10, 100:15 or 100:20. Natural graphite microspheres are mixed with the second bitumen in a mixer at a speed of 150-300 rpm (e.g., 150, 200, 250, or 300 rpm) for a mixing time of 60-120 min (e.g., 60, 80, 100, or 120 min). The densification treatment is performed at a pressure of 100-150 MPa (e.g., 100, 110, 120, 130, 140, or 150 MPa), a temperature of 250-350℃ (e.g., 250, 300, or 350℃), and a treatment time of 60-120 min (e.g., 60, 80, 100, or 120 min).

[0032] By filling with asphalt, the internal porosity of natural graphite particles is greatly reduced, which alleviates particle cracking caused by uneven stress during the cycle and significantly improves the cycle life.

[0033] In some embodiments, the step of mixing and granulating the precursor with artificial graphite to obtain secondary particle composite graphite includes: crushing and shaping coke to obtain coke powder as raw material for artificial graphite; mixing the coke powder, the precursor, and a third bitumen to obtain a second mixture; granulating the second mixture according to a heating curve to obtain granulated composite powder; and graphitizing the granulated composite powder to obtain secondary particle composite graphite.

[0034] The coke includes one or more of needle coke, petroleum coke, and coal-based pitch coke. The average particle size of the coke powder used as raw material for artificial graphite is 8μm-10μm, for example, 8μm, 9μm, or 10μm. The third pitch is, for example, petroleum pitch and / or coal tar pitch, and the softening point of the third pitch is 150℃-250℃, for example, 150℃, 200℃, or 250℃, preferably 180℃, and the quinoline insoluble content is ≤1%. The mass ratio of coke powder to precursor is 30:70-75:25, for example, 30:70, 40:60, 50:50, 60:40, 70:30 or 75:25, etc. The mass ratio of the sum of coke powder and precursor to third pitch is 100:(3-20), for example, 100:3, 100:5, 100:10, 100:15 or 100:20, etc., preferably 100:(5-15). The heating curve involves rapidly heating from room temperature to 420℃-480℃ (e.g., 420℃, 440℃, 460℃, or 480℃) at a rate of 5℃ / min-10℃ / min, followed by a slow heating to 680℃-720℃ (e.g., 680℃, 700℃, or 720℃) at a rate of 1℃ / min-5℃ / min, and holding at this temperature for 3h-10h (e.g., 3h, 5h, 7h, or 10h). The graphitization treatment temperature is 2800℃-3200℃ (e.g., 2800℃, 3000℃, or 3200℃), and the time is 2h-10h (e.g., 2h, 4h, 6h, 8h, or 10h).

[0035] By mixing and granulating densified natural graphite with artificial graphite, a composite graphite of natural and artificial secondary particles is obtained. This can improve the isotropy of the material and combine the advantages of natural graphite (high capacity, high compaction, and low cost) with the advantages of artificial graphite (high performance and long cycle life). At the same time, natural graphite can provide lubrication for artificial graphite during rolling, further improving the powder compaction density of the composite material.

[0036] In some embodiments, fusing the secondary particle composite graphite with graphene to obtain a fused material includes: dissolving graphene in a solvent to prepare a graphene solution; adding the secondary particle composite graphite and a binder to the graphene solution to obtain a mixed slurry; and performing a fusion reaction on the mixed slurry to obtain the fused material.

[0037] The solvent includes one or more of water, methanol, ethanol, or N-methylpyrrolidone, such as water and ethanol. The mass ratio of graphene to solvent is (5-8):100, such as 5:100, 6:100, 7:100, or 8:100. The binder includes one or more of sodium carboxymethyl cellulose, stearic acid, polyvinyl alcohol, phenolic resin, epoxy resin, glucose, or starch, such as epoxy resin and phenolic resin. The mass ratio of secondary particle composite graphite, graphene, and binder is 100:(5-20):(1-10), such as 100:5:1, 100:10:3, 100:15:7, or 100:20:10, preferably 100:(5-8):(2-8). The mixed slurry is fused in a fusion machine with a rotation speed of 50 r / min to 200 r / min, such as 50 r / min, 100 r / min, 150 r / min or 200 r / min, and a fusion time of 5 min to 30 min, such as 5 min, 10 min, 15 min, 20 min or 30 min.

[0038] The softening point of the first bitumen is 60℃-80℃, for example, 60℃, 70℃, or 80℃, and the quinoline insoluble content is ≤1%. The mass ratio of the first bitumen to the secondary particle composite graphite is (2-10):100, for example, 2:100, 4:100, 6:100, 8:100, or 10:100, preferably (3-8):100. The fusion is carbonized in a tube furnace under inert gas protection, the inert gas including nitrogen and / or argon; the carbonization temperature is 800℃-1200℃, for example, 800℃, 1000℃, or 1200℃, the heating rate is 5℃ / min-10℃ / min, for example, 5℃ / min, 7℃ / min, or 10℃ / min, and the treatment time is 1h-10h, for example, 1h, 2h, 5h, or 10h.

[0039] After coating the composite material with graphene pitch in a double layer, a high-performance composite graphite material with high specific capacity, high compaction, high initial efficiency, long cycle life and high rate performance can be obtained at a low cost.

[0040] In some embodiments of this application, a battery is provided, comprising: a positive electrode, a separator, a negative electrode, and an electrolyte, wherein the negative electrode comprises the negative electrode material described in any embodiment.

[0041] The battery stacking type is such as wound battery or stacked battery, and the structure type is such as prismatic battery, pouch battery or cylindrical battery, etc., without specific limitations. The battery has a long cycle life, high specific capacity and good fast charging performance.

[0042] Example 1

[0043] S1. Take 100g of natural graphite microspheres with a D50 of 8μm and 10g of petroleum asphalt with a softening point of 65℃ and place them in a mixer. Set the speed to 150r / min and mix for 90min to obtain the first mixture.

[0044] S2. The first mixture is placed in a hot isostatic press and heated to 250°C under a pressure of 100MPa. The temperature and pressure are maintained for 60 minutes. After cooling to room temperature, the mixture is broken up and sieved to obtain a precursor of dense natural graphite filled with asphalt.

[0045] S3. Take needle coke, crush and shape it to obtain 150g of coke powder with a D50 of 8μm, and place it in a mixer with 50g of precursor and 16g of petroleum asphalt with a softening point of 180℃. Set the speed to 150 r / min and mix for 90min to obtain the second mixture.

[0046] S4. Place the second mixture in a granulation vessel and heat it from room temperature to 450°C at a rate of 7°C / min, then heat it from 450°C to 700°C at a rate of 2°C / min, and keep it at 700°C for 5 hours. During the granulation process, the stirring speed is 100 rpm to obtain granulated composite powder.

[0047] S5. Place the granulated composite powder in a graphitization furnace and treat it at 3100℃ for 4 hours to graphitize it. After cooling, secondary granular composite graphite is obtained.

[0048] S6. Dissolve 6g of graphene powder in 100mL of ethanol and stir until homogeneous to obtain a graphene solution.

[0049] S7. Take 100g of secondary granular composite graphite and 3g of stearic acid and add them to the graphene solution. Stir evenly to prepare a mixed slurry of composite graphite and graphene.

[0050] S8. Place the mixed slurry in a fusion machine, rotate at 150 r / min, and carry out the fusion reaction for 20 min to obtain a fusion of graphene and natural and artificial composite graphite.

[0051] S9. 106g of the fusion mixture and 3g of petroleum asphalt with a softening point of 80℃ were placed in a tube furnace under a nitrogen atmosphere and heated to 800℃ for 2 hours at a rate of 10℃ / min to obtain a natural and artificial composite graphite anode material with a graphene double-layer coating, wherein the mass percentage of the graphene layer is 5.6% and the mass percentage of the asphalt layer is 1.4%. Figure 1 The image shown is an electron microscope image of the negative electrode material prepared in Example 1.

[0052] Example 2 S1. Take 100g of natural graphite microspheres with a D50 of 10μm and 15g of petroleum asphalt with a softening point of 65℃ and place them in a mixer. Set the speed to 150 r / min and mix for 90min to obtain the first mixture.

[0053] S2. The first mixture is placed in a hot isostatic press and heated to 250°C under a pressure of 120 MPa. The temperature and pressure are maintained for 90 minutes. After cooling to room temperature, the mixture is broken up and sieved to obtain a precursor of dense natural graphite filled with asphalt.

[0054] S3. Take needle coke, crush and shape it to obtain 60g of coke powder with a D50 of 10μm, and place it in a mixer with 140g of precursor and 24g of petroleum asphalt with a softening point of 180℃. Set the speed to 150 r / min and mix for 90min to obtain the second mixture.

[0055] S4. Place the second mixture in a granulation vessel and heat it from room temperature to 450°C at a rate of 7°C / min, then heat it from 450°C to 700°C at a rate of 2°C / min, and keep it at 700°C for 5 hours. During the granulation process, the stirring speed is 100 rpm to obtain granulated composite powder.

[0056] S5. Place the granulated composite powder in a graphitization furnace and treat it at 3000℃ for 4 hours to graphitize it. After cooling, secondary granular composite graphite is obtained.

[0057] S6. Dissolve 8g of graphene powder in 100mL of ethanol and stir until homogeneous to obtain a graphene solution.

[0058] S7. Take 100g of secondary granular composite graphite and 4g of phenolic resin and add them to the graphene solution. Stir evenly to prepare a mixed slurry of composite graphite and graphene.

[0059] S8. Place the mixed slurry in a fusion machine, rotate at 150 r / min, and carry out the fusion reaction for 20 min to obtain a fusion of graphene and natural and artificial composite graphite.

[0060] S9. Take 108g of the fusion material and 5g of petroleum asphalt with a softening point of 60℃ and place them in a tube furnace under a nitrogen atmosphere. Heat the furnace to 800℃ at a rate of 10℃ / min for 2 hours to obtain a natural and artificial composite graphite anode material with a graphene double layer coating. The graphene layer accounts for 7.2% of the mass and the asphalt layer accounts for 2.3% of the mass.

[0061] Example 3 S1. Take 100g of natural graphite microspheres with a D50 of 8μm and 10g of petroleum asphalt with a softening point of 65℃ and place them in a mixer. Set the speed to 150 r / min and mix for 90min to obtain the first mixture.

[0062] S2. The first mixture is placed in a hot isostatic press and heated to 250°C under a pressure of 100MPa. The temperature and pressure are maintained for 60 minutes. After cooling to room temperature, the mixture is broken up and sieved to obtain a precursor of dense natural graphite filled with asphalt.

[0063] S3. Take needle coke, crush and shape it to obtain 100g of coke powder with a D50 of 8μm, and place it in a mixer with 100g of precursor and 16g of petroleum asphalt with a softening point of 180℃. Set the speed to 150 r / min and mix for 90min to obtain the second mixture.

[0064] S4. Place the second mixture in a granulation vessel and heat it from room temperature to 450°C at a rate of 7°C / min, then heat it from 450°C to 700°C at a rate of 2°C / min, and keep it at 700°C for 5 hours. During the granulation process, the stirring speed is 100 rpm to obtain granulated composite powder.

[0065] S5. Place the granulated composite powder in a graphitization furnace and treat it at 3100℃ for 4 hours to graphitize it. After cooling, secondary granular composite graphite is obtained.

[0066] S6. Dissolve 6g of graphene powder in 100mL of ethanol and stir until homogeneous to obtain a graphene solution.

[0067] S7. Take 100g of secondary granular composite graphite and 3g of stearic acid and add them to the graphene solution. Stir evenly to prepare a mixed slurry of composite graphite and graphene.

[0068] S8. Place the mixed slurry in a fusion machine, rotate at 150 r / min, and carry out the fusion reaction for 20 min to obtain a fusion of graphene and natural and artificial composite graphite.

[0069] S9. Take 106g of the fusion material and 3g of petroleum asphalt with a softening point of 80℃ and place them in a tube furnace under a nitrogen atmosphere. Heat the furnace to 800℃ at a rate of 10℃ / min for 2 hours to obtain a natural and artificial composite graphite anode material with asphalt and graphene double-layer coating. The graphene layer accounts for 5.6% of the mass and the asphalt layer accounts for 1.4% of the mass.

[0070] Example 4 S1. Take 100g of natural graphite microspheres with a D50 of 8μm and 8g of petroleum asphalt with a softening point of 65℃ and place them in a mixer. Set the speed to 150 r / min and mix for 90min to obtain the first mixture.

[0071] S2. The first mixture is placed in a hot isostatic press and heated to 250°C under a pressure of 100MPa. The temperature and pressure are maintained for 60 minutes. After cooling to room temperature, the mixture is broken up and sieved to obtain a precursor of dense natural graphite filled with asphalt.

[0072] S3. Take needle coke, crush and shape it to obtain 150g of coke powder with a D50 of 8μm, and place it in a mixer with 50g of precursor and 6g of petroleum asphalt with a softening point of 180℃. Set the speed to 150 r / min and mix for 90min to obtain the second mixture.

[0073] S4. Place the second mixture in a granulation vessel and heat it from room temperature to 450°C at a rate of 7°C / min, then heat it from 450°C to 700°C at a rate of 2°C / min, and keep it at 700°C for 5 hours. During the granulation process, the stirring speed is 100 rpm to obtain granulated composite powder.

[0074] S5. Place the granulated composite powder in a graphitization furnace and treat it at 3100℃ for 4 hours to graphitize it. After cooling, secondary granular composite graphite is obtained.

[0075] S6. Dissolve 5g of graphene powder in 100mL of ethanol and stir until homogeneous to obtain a graphene solution.

[0076] S7. Take 100g of secondary granular composite graphite and 1g of stearic acid and add them to the graphene solution. Stir evenly to prepare a mixed slurry of composite graphite and graphene.

[0077] S8. Place the mixed slurry in a fusion machine, rotate at 150 r / min, and carry out the fusion reaction for 20 min to obtain a fusion of graphene and natural and artificial composite graphite.

[0078] S9. Take 105g of the fusion material and 2.1g of petroleum asphalt with a softening point of 80℃ and place them in a tube furnace under a nitrogen atmosphere. Heat the furnace to 800℃ at a rate of 10℃ / min for 2 hours to obtain a natural and artificial composite graphite anode material with a graphene double layer coating. The graphene layer accounts for 4.7% of the mass and the asphalt layer accounts for 2% of the mass.

[0079] Example 5 S1. Take 100g of natural graphite microspheres with a D50 of 8μm and 20g of petroleum asphalt with a softening point of 65℃ and place them in a mixer. Set the speed to 150 r / min and mix for 90min to obtain the first mixture.

[0080] S2. The first mixture is placed in a hot isostatic press and heated to 250°C under a pressure of 100MPa. The temperature and pressure are maintained for 60 minutes. After cooling to room temperature, the mixture is broken up and sieved to obtain a precursor of dense natural graphite filled with asphalt.

[0081] S3. Take needle coke, crush and shape it to obtain 150g of coke powder with a D50 of 8μm, and place it in a mixer with 50g of precursor and 40g of petroleum asphalt with a softening point of 180℃. Set the speed to 150 r / min and mix for 120min to obtain the second mixture.

[0082] S4. Place the second mixture in a granulation vessel and heat it from room temperature to 450°C at a rate of 7°C / min, then heat it from 450°C to 700°C at a rate of 2°C / min, and keep it at 700°C for 5 hours. During the granulation process, the stirring speed is 100 rpm to obtain granulated composite powder.

[0083] S5. Place the granulated composite powder in a graphitization furnace and treat it at 3100℃ for 4 hours to graphitize it. After cooling, a graphene solution is obtained.

[0084] S6. Dissolve 20g of graphene powder in 150mL of ethanol and stir until homogeneous to obtain a graphene solution.

[0085] S7. Take 100g of graphene solution and 10g of stearic acid and add them to the graphene solution. Stir evenly to prepare a mixed slurry of composite graphite and graphene.

[0086] S8. Place the mixed slurry from the step into a fusion machine, and carry out the fusion reaction at a speed of 150 r / min for 30 min to obtain a graphene fusion product of natural and artificial composite stone.

[0087] S9. Take 120g of the fusion material and 12g of petroleum asphalt with a softening point of 80℃ and place them in a tube furnace under a nitrogen atmosphere. Heat the furnace to 800℃ at a rate of 10℃ / min for 2 hours to obtain a natural and artificial composite graphite anode material with a graphene double layer coating. The graphene layer accounts for 15.2% of the mass and the asphalt layer accounts for 9.1% of the mass.

[0088] Comparative Example 1 S1. Take 100g of natural graphite microspheres with a D50 of 8μm and 10g of petroleum asphalt with a softening point of 65℃ and place them in a mixer. Set the speed to 150 r / min and mix for 90min to obtain a mixture.

[0089] S2. Place the mixture in a hot isostatic press, heat it to 250°C under 100MPa pressure, keep it at the temperature and pressure for 60 minutes, cool it to room temperature, and then break it up and sieve it to obtain a dense natural graphite precursor filled with asphalt.

[0090] S3. The densified natural graphite precursor is placed in a graphitization furnace and treated at 2800℃ for 4 hours to perform graphitization. After cooling, single-particle densified natural graphite is obtained.

[0091] S4. Dissolve 6g of graphene powder in 100mL of ethanol and stir until homogeneous to obtain a graphene solution.

[0092] S5. Take 100g of densified natural graphite and 3g of stearic acid and add them to the graphene solution. Stir evenly to make a mixed slurry of natural graphite and graphene.

[0093] S6. Place the mixed slurry in a fusion machine, rotate at 150 r / min, and perform a fusion reaction for 20 min to obtain a fusion of graphene and densified natural graphite.

[0094] S7. Take 106g of the fusion material and 3g of petroleum asphalt with a softening point of 80℃ and place them in a tube furnace under a nitrogen atmosphere. Heat the furnace to 800℃ at a rate of 10℃ / min for 2 hours to obtain a dense natural graphite anode material with a graphene double-layer coating of asphalt, wherein the mass ratio of the graphene layer is 5.6% and the mass ratio of the asphalt layer is 1.4%.

[0095] Comparative Example 2 S1. Take needle coke, crush and shape it to obtain 200g of coke aggregate with D50 of 8μm, and place it in a mixer with 16g of petroleum asphalt with a softening point of 180℃. Set the speed to 150 r / min and mix for 90min to obtain a mixture.

[0096] S2. Place the mixture in a granulation vessel and raise the temperature from room temperature to 450°C at a rate of 7°C / min, then raise the temperature from 450°C to 700°C at a rate of 2°C / min, and keep it at 700°C for 5 hours. During the granulation process, the stirring speed is 100 rpm to obtain the secondary granulated coke composite.

[0097] S3. The secondary particulate coke composite was placed in a graphitization furnace and treated at 3100℃ for 4 hours to graphitize it. After cooling, secondary particulate artificial graphite was obtained.

[0098] S4. Dissolve 6g of graphene powder in 100mL of ethanol and stir until homogeneous to obtain a graphene solution.

[0099] S5. Take 100g of secondary granular artificial graphite and 3g of stearic acid and add them to the graphene solution. Stir evenly to make a mixed slurry of artificial graphite and graphene.

[0100] S6. Place the mixed slurry in a fusion machine, rotate at 150 r / min, and carry out the fusion reaction for 20 min to obtain a graphene-artificial graphite fusion.

[0101] S7. Take 106g of the fusion material and 3g of petroleum asphalt with a softening point of 80℃ and place them in a tube furnace under a nitrogen atmosphere. Heat the furnace to 800℃ at a rate of 10℃ / min for 2 hours to obtain a bilayer artificial graphite anode material with asphalt and graphene coating. The graphene layer accounts for 5.6% of the mass and the asphalt layer accounts for 1.4% of the mass.

[0102] Comparative Example 3 S1. Take 100g of natural graphite microspheres with a D50 of 8μm and 10g of petroleum asphalt with a softening point of 65℃ and place them in a mixer. Set the speed to 150 r / min and mix for 90min to obtain a mixture.

[0103] S2. Place the mixture in a hot isostatic press, heat it to 250°C under 100MPa pressure, keep it at the temperature and pressure for 60 minutes, cool it to room temperature, and then break it up and sieve it to obtain a dense natural graphite precursor filled with asphalt.

[0104] S3. Take needle coke, crush and shape it to obtain 150g of coke aggregate with D50 of 8μm, 50g of densified natural graphite precursor and 16g of petroleum asphalt with softening point of 180℃. Place them in a mixer, set the speed to 150 r / min, mix for 90min to obtain a mixture.

[0105] S4. Place the mixture in a granulation vessel and raise the temperature from room temperature to 450°C at a rate of 7°C / min, then raise the temperature from 450°C to 700°C at a rate of 2°C / min, and keep it at 700°C for 5 hours. During the granulation process, the stirring speed is 100 rpm to obtain secondary granulated natural graphite coke composite.

[0106] S5. The secondary particle natural graphite coke composite was placed in a graphitization furnace and treated at 3100℃ for 4 hours for graphitization. After cooling, secondary particle natural and artificial composite graphite was obtained.

[0107] S6. Take 100g of secondary granular natural and artificial composite graphite and 3g of petroleum asphalt with a softening point of 80℃ and place them in a tube furnace under a nitrogen atmosphere. Heat the furnace to 800℃ at a rate of 10℃ / min for 2 hours to obtain asphalt-coated natural and artificial composite graphite anode material.

[0108] Comparative Example 4 S1. Take needle coke, crush and shape it to obtain 150g of coke aggregate with D50 of 8μm, 50g of natural graphite microspheres with D50 of 8μm, and 16g of petroleum asphalt with a softening point of 180℃. Place them in a mixer, set the speed to 150 r / min, and mix for 90min to obtain a mixture.

[0109] S2. Place the mixture in a granulation vessel and raise the temperature from room temperature to 450°C at a rate of 7°C / min, then raise the temperature from 450°C to 700°C at a rate of 2°C / min, and keep it at 700°C for 5 hours. During the granulation process, the stirring speed is 100 rpm to obtain secondary granulated natural graphite coke composite.

[0110] S3. The secondary particle natural graphite coke composite was placed in a graphitization furnace and treated at 3100℃ for 4 hours for graphitization. After cooling, secondary particle natural and artificial composite graphite was obtained.

[0111] S4. Dissolve 6g of graphene powder in 100mL of ethanol and stir until homogeneous to obtain a graphene solution.

[0112] S5. Take 100g of secondary granular natural and artificial composite graphite and 3g of stearic acid and add them to the graphene solution. Stir evenly to make a composite graphite and graphene mixed slurry.

[0113] S6. Place the mixed slurry in a fusion machine, rotate at 150 r / min, and carry out the fusion reaction for 20 min to obtain a fusion of graphene and natural and artificial composite graphite.

[0114] S7. Take 106g of the fusion material and 3g of petroleum asphalt with a softening point of 80℃ and place them in a tube furnace under a nitrogen atmosphere. Heat the furnace to 800℃ at a rate of 10℃ / min for 2 hours to obtain a natural (non-densified) and artificial composite graphite anode material with a graphene double layer coating. The graphene layer accounts for 5.6% of the mass and the asphalt layer accounts for 1.4% of the mass.

[0115] Comparative Example 5 S1. Take 100g of natural graphite microspheres with a D50 of 8μm and 10g of petroleum asphalt with a softening point of 65℃ and place them in a mixer. Set the speed to 150 r / min and mix for 90min to obtain a mixture.

[0116] S2. Place the mixture in a hot isostatic press, heat it to 250°C under 100 MPa pressure, keep it at the temperature and pressure for 60 minutes, cool it to room temperature, and then break it up and sieve it to obtain a dense natural graphite precursor filled with asphalt.

[0117] S3. Take needle coke, crush and shape it to obtain 150g of coke aggregate with D50 of 8μm, 50g of densified natural graphite precursor and 16g of petroleum asphalt with softening point of 180℃. Place them in a mixer, set the speed to 150 r / min, mix for 90min to obtain a mixture.

[0118] S4. Place the mixture in a granulation vessel and raise the temperature from room temperature to 450°C at a rate of 7°C / min, then raise the temperature from 450°C to 700°C at a rate of 2°C / min, and keep it at 700°C for 5 hours. During the granulation process, the stirring speed is 100 rpm to obtain secondary granulated natural graphite coke composite.

[0119] S5. The secondary particle natural graphite coke composite was placed in a graphitization furnace and treated at 3100℃ for 4 hours for graphitization. After cooling, secondary particle natural and artificial composite graphite was obtained.

[0120] S6. Dissolve 6g of graphene powder in 100mL of ethanol and stir until homogeneous to obtain a graphene solution.

[0121] S7. Take 100g of secondary granular natural and artificial composite graphite and 3g of stearic acid and add them to the graphene solution. Stir evenly to make a composite graphite and graphene mixed slurry.

[0122] S8. Place the mixed slurry in a fusion machine, rotate at 150 r / min, and carry out the fusion reaction for 20 min to obtain a fusion of graphene and natural and artificial composite graphite.

[0123] S9. The fusion material is placed in a tube furnace under a nitrogen atmosphere and heated to 800℃ at a rate of 10℃ / min for 2 hours to obtain graphene-coated natural and artificial composite graphite anode material.

[0124] Comparative Example 6 S1. Take 100g of natural graphite microspheres with a D50 of 8μm and 10g of petroleum asphalt with a softening point of 65℃ and place them in a mixer. Set the speed to 150 r / min and mix for 90min to obtain a mixture.

[0125] S2. Place the mixture in a hot isostatic press, heat it to 250°C under 100MPa pressure, keep it at the temperature and pressure for 60 minutes, cool it to room temperature, and then break it up and sieve it to obtain a dense natural graphite precursor filled with asphalt.

[0126] S3. Take needle coke, crush and shape it to obtain 150g of coke aggregate with D50 of 8μm, 50g of densified natural graphite precursor and 16g of petroleum asphalt with softening point of 180℃. Place them in a mixer, set the speed to 150 r / min, mix for 90min to obtain a mixture.

[0127] S4. Place the mixture in a granulation vessel and raise the temperature from room temperature to 450°C at a rate of 7°C / min, then raise the temperature from 450°C to 700°C at a rate of 2°C / min, and keep it at 700°C for 5 hours. During the granulation process, the stirring speed is 100 rpm to obtain secondary granulated natural graphite coke composite.

[0128] S5. The secondary particle natural graphite coke composite was placed in a graphitization furnace and treated at 3100℃ for 4 hours for graphitization. After cooling, secondary particle natural and artificial composite graphite was obtained.

[0129] S6. Take 100g of secondary granular natural and artificial composite graphite, 6g of graphene powder and 3g of petroleum asphalt with a softening point of 80℃ and put them into a mixer. Set the speed to 150 r / min and mix for 60min to obtain a mixture.

[0130] S7. The mixture is placed in a tube furnace under a nitrogen atmosphere and heated to 800℃ at a rate of 10℃ / min for 2 hours to obtain a natural and artificial composite graphite anode material with graphene and asphalt co-coated, wherein the mass percentage of graphene is 5.6% and the mass percentage of asphalt is 1.4%.

[0131] Comparative Example 7 S1. Take 100g of natural graphite microspheres with a D50 of 8μm and 10g of petroleum asphalt with a softening point of 65℃ and place them in a mixer. Set the speed to 150 r / min and mix for 90min to obtain a mixture.

[0132] S2. Place the mixture in a hot isostatic press, heat it to 250°C under 100MPa pressure, keep it at the temperature and pressure for 60 minutes, cool it to room temperature, and then break it up and sieve it to obtain a dense natural graphite precursor filled with asphalt.

[0133] S3. Take needle coke, crush and shape it to obtain 150g of coke aggregate with D50 of 8μm, 50g of densified natural graphite precursor and 16g of petroleum asphalt with softening point of 180℃. Place them in a mixer, set the speed to 150 r / min, mix for 90min to obtain a mixture.

[0134] S4. Place the mixture in a granulation vessel and raise the temperature from room temperature to 450°C at a rate of 7°C / min, then raise the temperature from 450°C to 700°C at a rate of 2°C / min, and keep it at 700°C for 5 hours. During the granulation process, the stirring speed is 100 rpm to obtain secondary granulated natural graphite coke composite.

[0135] S5. The secondary particle natural graphite coke composite was placed in a graphitization furnace and treated at 3100℃ for 4 hours for graphitization. After cooling, secondary particle natural and artificial composite graphite was obtained.

[0136] S6. Take 100g of secondary granular natural and artificial composite graphite and 3g of petroleum asphalt with a softening point of 80℃, mix them evenly, and place them in a tube furnace under a nitrogen atmosphere. Heat the mixture to 800℃ at a rate of 10℃ / min for 2 hours to obtain asphalt-coated natural and artificial composite graphite anode material.

[0137] S7. Dissolve 6g of graphene powder in 100mL of ethanol and stir until homogeneous to obtain a graphene solution.

[0138] S8. Take 103g of asphalt-coated secondary granules of natural and artificial composite graphite and 3g of stearic acid, add them to the graphene solution, and stir evenly to make a composite graphite and graphene mixed slurry.

[0139] S9. Place the mixed slurry in a fusion machine, rotate at 150 r / min, and perform a fusion reaction for 20 min to obtain a fusion of graphene and natural and artificial composite graphite.

[0140] S10. Take 109g of the fusion material and place it in a tube furnace under a nitrogen atmosphere. Heat it to 600℃ at a rate of 10℃ / min for 2 hours to obtain a natural and artificial composite graphite anode material with graphene and asphalt double-layer coating. The graphene layer accounts for 5.6% of the mass and the asphalt layer accounts for 1.4% of the mass.

[0141] The particle size distribution of the negative electrode materials in Examples 1-5 and Comparative Examples 1-7 was tested using a Malvern laser particle size analyzer, and the powder compaction density was tested using a powder compaction density analyzer.

[0142] Half-cell tests were conducted on the negative electrode materials of Examples 1-5 and Comparative Examples 1-7. The negative electrode material, conductive carbon black (SP), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were mixed uniformly in a ratio of 96.5%:1%:1%:1.5%, coated onto copper foil, and then rolled and dried to obtain the negative electrode sheet. The lithium metal sheet was used as the counter electrode, and the electrolyte was 1M LiPF6+EC:DEC:DMC = 1:1:1 (volume ratio). The separator was an Enjie 25μm PP separator. Button cells were fabricated in a glove box, and charge-discharge tests were conducted on Arbin's BT2000 equipment. The charge-discharge voltage range was 0.005V-2V, and the charge-discharge current was 0.1C. The initial discharge capacity and efficiency were obtained from the tests.

[0143] Full-cell tests were conducted on the anode materials of Examples 1-5 and Comparative Examples 1-7. The anode material was used as the anode, lithium iron phosphate material as the cathode, 1M LiPF6+EC:DEC:DMC (volume ratio 1:1:1) solution as the electrolyte, and Enjie ND7M22O as the separator. The cells were assembled into 1.5Ah soft-pack full cells. The tests were conducted using Arbin BT2000 equipment, with a voltage range of 2.5-3.65V. The cells were charged and discharged at 25°C at 1 / 3C and 3C rates, and then charged and discharged at 1C rate at 25°C. The rate and low-temperature performance were obtained from the tests.

[0144] Table 1 Test Table of Physicochemical and Electrochemical Properties of Anode Materials

[0145] The test results above are shown in Table 1. It can be seen that the specific capacity of the negative electrode materials in Examples 1-5 is significantly improved, the first efficiency is also high, and the fast charging and cycle performance is excellent, which solves the problem that graphite materials are difficult to achieve in a balanced way.

[0146] Comparative Example 1 only underwent densification of single-particle natural graphite and surface coating with graphene pitch, without adding artificial graphite for mixing and granulation. The material had a high specific capacity, but poor fast-charging performance and cycle life.

[0147] Comparative Example 2 involved coating secondary granular artificial graphite with graphene pitch without adding densified natural graphite for mixing and granulation. The ratio and cycle performance were good, but the discharge specific capacity and powder compaction density were low because there was no natural graphite to provide a capacity base and rolling lubrication effect.

[0148] Comparative Example 3 only had pitch coating on natural and artificial composite graphite, but no graphene coating, and the material had a lower specific capacity.

[0149] The natural graphite core of Comparative Example 4, without densification treatment, was mixed with artificial graphite, granulated, and coated with a double layer of graphene pitch. Although it still had a high specific capacity, its cycle performance was poor.

[0150] Comparative Example 5 only had a single layer of graphene coating on the outer layer and no asphalt coating. Although the material had a high specific capacity, the graphene layer was exposed to the electrolyte, resulting in a large amount of lithium ion consumption, which led to a low initial efficiency and poor cycle performance.

[0151] In Comparative Example 6, graphene was mixed with asphalt and then coated onto the composite graphite. As a result, some of the graphene coating was exposed on the surface of the negative electrode material, leading to variations in the material's first-efficiency and cycle performance.

[0152] Comparative Example 7 first coated the material with asphalt, and then coated it with graphene. Similar to Comparative Example 5, the graphene layer was directly exposed in the electrolyte, and the material had poor initial efficiency and cycle life.

[0153] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of this application is limited to these examples; under the concept of this application, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of different aspects of the embodiments of this application as described above, which are not provided in detail for the sake of brevity.

[0154] Furthermore, given that details have been set forth to describe exemplary embodiments of this application, it will be apparent to those skilled in the art that embodiments of this application may be practiced without these details or with variations thereof. Therefore, these descriptions should be considered illustrative rather than restrictive.

[0155] To simplify the description and discussion, and to avoid obscuring the embodiments of this application, well-known power / ground connections to other components may or may not be shown in the provided drawings. Furthermore, the apparatus may be shown in block diagram form to avoid obscuring the embodiments of this application, and this also takes into account the fact that the details of implementation of these block diagram apparatuses are highly dependent on the platform on which the embodiments of this application will be implemented (i.e., these details should be fully understood by those skilled in the art). While specific details have been set forth to describe exemplary embodiments of this application, it will be apparent to those skilled in the art that the embodiments of this application may be implemented without these specific details or with variations thereof. Therefore, these descriptions should be considered illustrative rather than restrictive.

[0156] Although this application has been described in conjunction with specific embodiments thereof, many substitutions, modifications, and variations of these embodiments will be apparent to those skilled in the art from the foregoing description. The embodiments of this application are intended to cover all such substitutions, modifications, and variations falling within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the embodiments of this application should be included within the protection scope of this application.

Claims

1. A negative electrode material, characterized in that, It includes a core, a first shell covering the core, and a second shell covering the first shell; the material of the core includes secondary particle composite graphite, which is a mixture of densified natural graphite and artificial graphite; the material of the first shell includes graphene; and the material of the second shell includes first bitumen.

2. A method for preparing the negative electrode material according to claim 1, characterized in that, include: Precursors for preparing densified natural graphite; The precursor is mixed with artificial graphite and granulated to obtain secondary particle composite graphite. The secondary particle composite graphite is fused with graphene to obtain a fused material; The fusion mixture is mixed with the first bitumen and then subjected to carbonization treatment to obtain the negative electrode material.

3. The method for preparing the negative electrode material according to claim 2, characterized in that, The precursor for preparing densified natural graphite includes: Natural graphite microspheres are mixed with a second bitumen to obtain a first mixture; The first mixture was subjected to densification treatment by pressurization and heating to obtain a precursor of densified natural graphite.

4. The method for preparing the negative electrode material according to claim 3, characterized in that, The average particle size of the natural graphite microspheres is 5μm-15μm; the softening point of the second asphalt is 60℃-90℃, and the quinoline insoluble content is ≤1%; the mass ratio of the natural graphite microspheres to the second asphalt is 100:(8-20). The natural graphite microspheres are mixed with the second asphalt in a mixer at a speed of 150 r / min-300 r / min and a mixing time of 60 min-120 min. The densification treatment is carried out at a pressure of 100 MPa-150 MPa, a temperature of 250℃-350℃, and a treatment time of 60 min-120 min.

5. The method for preparing the negative electrode material according to claim 2, characterized in that, The process of mixing and granulating the precursor with artificial graphite to obtain secondary particle composite graphite includes: Coke is crushed and shaped to obtain coke powder; The coke powder, the precursor, and the third pitch are mixed to obtain a second mixture; The second mixture is heated and granulated according to the heating curve to obtain granulated composite powder; The granulated composite powder is graphitized to obtain secondary granular composite graphite.

6. The method for preparing the negative electrode material according to claim 5, characterized in that, The average particle size of the coke powder is 8μm-10μm; the softening point of the third pitch is 150℃-250℃, and the quinoline insoluble content is ≤1%; the mass ratio of the coke powder to the precursor is 30:70-75:25, and the mass ratio of the sum of the coke powder and the precursor to the third pitch is 100:(3-20). The heating curve is a rapid increase from room temperature to 420℃-480℃, followed by a slow increase to 680℃-720℃, and a holding time of 3h-10h; the graphitization treatment temperature is 2800℃-3200℃, and the time is 2h-10h.

7. The method for preparing the negative electrode material according to claim 2, characterized in that, The process of fusing the secondary particle composite graphite with graphene to obtain a fused material includes: Graphene is dissolved in a solvent to prepare a graphene solution; The secondary particle composite graphite and binder are added to the graphene solution to obtain a mixed slurry; The mixed slurry is subjected to a fusion reaction to obtain a fused product.

8. The method for preparing the negative electrode material according to claim 7, characterized in that, The solvent includes one or more of water, methanol, ethanol, or N-methylpyrrolidone, and the mass ratio of graphene to the solvent is (5-8):100; the binder includes one or more of sodium hydroxymethyl cellulose, stearic acid, polyvinyl alcohol, phenolic resin, epoxy resin, glucose, or starch, and the mass ratio of the secondary particle composite graphite, the graphene, and the binder is 100:(5-20):(1-10); The mixed slurry is fused in a fusion machine with a rotation speed of 50 r / min-200 r / min and a fusion time of 5 min-30 min.

9. The method for preparing the negative electrode material according to claim 2, characterized in that, The softening point of the first asphalt is 60℃-80℃, and the quinoline insoluble content is ≤1%; the mass ratio of the first asphalt to the secondary particle composite graphite is (2-10):

100. The fusion is carbonized in a tube furnace under inert gas protection, the inert gas including nitrogen and / or argon; the carbonization temperature is 800℃-1200℃, the heating rate is 5℃ / min-10℃ / min, and the treatment time is 1h-10h.

10. A battery, characterized in that, include: A positive electrode, a separator, a negative electrode, and an electrolyte, wherein the negative electrode comprises the negative electrode material as described in claim 1.